Cholelithiasis in patients treated with Glucagon-Like Peptide-1 Receptor: An updated meta-analysis of randomized controlled trials. (March 2020) - Nreu, Besmir; Dicembrini, Ilaria; Tinti, Federico; Mannucci, Edoardo; Monami, Matteo
Abstract: Glucagon-Like Peptide-1 Receptor Agonists (GLP1-RA) has been associated with cholelithiasis in a previous meta-analysis. The publication of new trials suggests the need for an update. We collected trials with GLP1-RA vs. other therapies, calculating Mantel-Haenszel odds ratio (MH-OR, 95%CI). GLP1-RA significantly increased the risk of cholelithiasis (MH-OR 1.28 [1.11, 1.48]).